Duration of Postdiarrheal Enteric Pathogen Carriage in Young Children in Low-resource Settings. (9th October 2020) - McMurry, Timothy L; McQuade, Elizabeth T Rogawski; Liu, Jie; Kang, Gagandeep; Kosek, Margaret N; Lima, Aldo A M; Bessong, Pascal O; Samie, Amidou; Haque, Rashidul; Mduma, Estomih R; Leite, Jose Paulo; Bodhidatta, Ladaporn; et al.
Abstract: Background: Prolonged enteropathogen shedding after diarrhea complicates the identification of etiology in subsequent episodes and is an important driver of pathogen transmission. A standardized approach has not been applied to estimate the duration of shedding for a wide range of pathogens. Methods: We used a multisite birth cohort of children 0–24 months of age from whom diarrheal and monthly nondiarrheal stools were previously tested by quantitative polymerase chain reaction for 29 enteropathogens. We modeled the probability of detection of the etiologic pathogen before and after diarrhea using a log-normal accelerated failure time survival model and estimated the median duration of pathogen carriage as well as differences in subclinical pathogen carriage 60 days after diarrhea onset in comparison to a prediarrhea baseline. Results: We analyzed 3247 etiologic episodes of diarrhea for the 9 pathogens with the highest attributable burdens of diarrhea. The median duration of postdiarrheal carriage varied widely by pathogen, from about 1 week for rotavirus (median, 8.1 days [95% confidence interval CI, 6.2–9.6]) to >1 month for Cryptosporidium (39.5 days [95% CI, 30.6–49.0]). The largest increases in subclinical pathogen carriage before and after diarrhea were seen for Cryptosporidium (prevalence difference between 30 days prior and 60 days after diarrhea onset, 0.30 [95% CI, .23–.39]) and Shigella (prevalence difference, 0.21 [95% CI, .16–.27]). Conclusions: Postdiarrheal shedding was widely variable between pathogens, with strikingly prolonged shedding seen for Cryptosporidium and Shigella . Targeted antimicrobial therapy and vaccination for these pathogens may have a relatively large impact on transmission. Abstract : In a multisite birth cohort study of children 0–24 months of age and with quantitative polymerase chain reaction detection of diarrheal pathogens, we estimate the duration of postdiarrheal carriage in low-resource settings, with strikingly prolonged shedding seen for Cryptosporidium and Shigella .